Comparability and feasibility of wrist- and hip-worn accelerometers in free-living adolescents. Issue 12 (December 2017) - Scott, Joseph J.; Rowlands, Alex V.; Cliff, Dylan P.; Morgan, Philip J.; Plotnikoff, Ronald C.; Lubans, David R.
Abstract: Objective: To determine the comparability and feasibility of wrist- and hip-worn accelerometers among free-living adolescents. Design: 89 adolescents (age = 13–14 years old) from eight secondary schools in New South Wales (NSW), Australia wore wrist-worn GENEActiv and hip-worn ActiGraph (GT3X+) accelerometers simultaneously for seven days and completed an accelerometry behavior questionnaire. Methods: Bivariate correlations between the wrist- and hip-worn out-put were used to determine concurrent validity. Paired samples t -test were used to compare minutes per day in moderate-to-vigorous physical activity (MVPA). Group means and paired sample t -tests were used to analyze participants' perceptions of the wrist- and hip-worn monitoring protocols to assist with determining the feasibility. Results: Wrist-worn accelerometry compared favorably with the hip-worn in average activity (r = 0.88, p < 0.001) and MVPA (r = 0.84 p < 0.001, mean difference = 3.54 min/day, SD = 12.37). The wrist-worn accelerometer had 50% fewer non-valid days (75 days, 12%) than the hip-worn accelerometer (n = 152, 24.4%). Participants reported they liked to wear the device on the wrist (p < 0.01), and that it was less uncomfortable (p = 0.02) and less embarrassing to wear on the wrist (p < 0.01). Furthermore, that they would be more willing to wear the device again on the wrist over the hip (p < 0.01). Conclusions: Our findings reveal there is a strong linear relationship between wrist- and hip-worn accelerometer out-put among adolescents in free-living conditions. Adolescent compliance was significantly higher with wrist placement, with participants reporting that it was more comfortable and less embarrassing to wear on the wrist.